Banco comunitário de desenvolvimento Jardim Botânico: gestão social comunitária e desenvolvimento local - Raposo, Jaciara Gomes (2014)
This work makes an analysis of the process of the social preparation of the Jardim Botânico Community Bank and of its social currency called the orquídea (orchid) in the community of São Rafael, a poor neighborhood in João Pessoa, Brazil, and of how the mechanisms of social community administration of this initiative of support and fomentation of local development are built. The community development banks belong to the field of solidarity finance as collective forms of organization of mutual aid which aim at guaranteeing access to credit and stimulating development in impoverished communities through the organization of the local economy generating new socio-economic interaction and building a new reality. We shall approach the institutional arrangement created by the community, the social management, the activities carried out, and the instruments utilized for promoting development in the community. It is a question of a qualitative, descriptive and exploratory case study through which we try to make a contribution to the understanding of the community development banks in the country.